Compositional changes of CH, O, and N moieties in petroleum ether-extractable portions from the three-step mild degradation of Dongming lignite. (15th March 2023) - Li, Yan-Jun; Zhao, Wei; Liu, Guang-Hui; An, Hao-Dong; Ma, Ya-Jun; Kang, Yu-Hong; Gao, Yong; Bai, Ni; Wang, Ding-Kai; Wei, Xian-Yong; Bai, Hong-Cun
Graphical abstract: Highlights: EPC and EPE are rich in short side-chain substituted aromatics. >C-O- and >C=O moieties predominate in EPE and EPCE . Ethanol involves in the cleavage reactions of >Cal -O- and >Cal -C< bridged bonds. EPs contain non-negligible oxynitrides, especially N 1 O 1 and N 2 O 1-4 . Abstract: Migration and distribution changes of CH, O, and N moieties in Dongming lignite (DL) derived petroleum ether-extractable portions (EPs), including cyclohexane (EPC ), ethanol (EPE ), and cyclohexane/ethanol (EPCE ) systems were focused on in this work. Overall, EPC and EPE are rich in aromatics with short side-chains, while EPCE has the highest aromaticity. The gas chromatograph/mass spectrometer (GC/MS) analysis indicated that CH, >C-O-, and >C=O are three main parts. Alkanes in EPC are mainly concentrated in C 11 - C 31 and the pristane/phytane ratio is 0.7, indicating the early anaerobic diagenesis of DL. Arenes are dominated by mono- to tricyclic compounds. The identification of these native compounds with low aromaticity implies the low coalification degree of DL. In addition, >C-O- and >C=O moieties predominate in EPE and EPCE . The differences in characteristic oxygenates, such as phenols and acetophenones, further indicated that ethanol involves in the cleavage of >Cal -O-Cal <, >Cal -O-Car <, and >Cal -Cal < bridged bonds in DL. GC/MS-undetectable oxynitrides, such as N 1 O 1 and N 2 O 1-4 species, were also discovered by Orbitrap MS. The compositional changes of O/ N -containing species are related to source differences: (1) Step 1: the release of intrinsic fragments, (2) Step 2: the cleavage of weak O/ N -containing covalent bonds, and (3) Step 3: the cleavage of covalent bonds with higher bond dissociation energies and the dissolution of macromolecules. The investigation on the changes of CH, O, and N moieties during the three-step mild degradation is beneficial to the secondary upgrading and value-added utilization of DL-derived soluble portions.